Exploring the impact of clothing insulation on thermal comfort evaluation using thermal manikins - Cernei Alexandru; Lacassagne Tom; Fagniez Thomas; Danca Paul; Georgescu Matei-Răzvan; Thevenet Frédéric; Verriele Marie; Nastase Ilinca (E3S Web of Conferences)
Thermal manikins are valuable tools used in advancing our understanding of thermal comfort. This study examines the effect of varying clothing insulation on the predicted degree of thermal comfort using a thermal manikin named MONICA (MONitoring Indoor Comfort and Air quality). The experiments were conducted in a controlled climate chamber with the room temperature maintained at 24 °C. Three different clothing configurations were tested: naked, summer clothes (0.2 clo), and winter office clothes (0.7 clo). The equivalent temperature was measured for each configuration and compared to the Predicted Mean Vote (PMV) values obtained simultaneously. Additionally, the study utilized the Background Oriented Schlieren (BOS) technique to visualize the thermally driven airflow around the manikin. The findings from this study confirm the effectiveness of the thermal manikin in simulating human thermal responses and provide valuable insights into the role of clothing insulation in thermal comfort assessments. The obtained results will be useful for choosing the right clothing insulation for future thermal comfort assessments with the manikin.